THE STAGES OF DEVELOPMENT THE CONCEPT "INDIVIDUALIZATION OF THE PROFESSIONAL TRAINING OF THE TEACHER" AS A SCIENTIFIC PROBLEM - CHERNIONKOV, Yaroslav Olexandrovych (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
It has been analyzed the content of the concept «Individualization of the professional training» as a scientific problem in various dictionaries and the works of eminent scholars from different periods, both foreign and domestic. It was indicated in the article that individualization is a consideration, in the process of training, the individual characteristics of the students in all its forms and methods, regardless of which features in any way taken into account. It was noted by the author that some scientist, under the concept of "individualization of training", understand the relative individualization, which is namely: focused on the individual psychological characteristics of the student; based on the individual differences of the future teachers; implemented the principle of individual approach, taking into account the individual characteristics of students in the process of learning in all its forms and methods no matter what are the characteristics and the extent to which they are recorded. According to the individualization of training we understand the organization of the message to students the appropriate expertise and the skills formation based on their individual characteristics, creating optimum conditions for the realization of the potential of each student. Personalization of the training does not allow to level differences between students, each student contributes to the development of their unique skills, focuses on preparations for the highly professional work. The main objectives, results and criteria of individualization of training are: improving the efficiency of vocational teacher training, creating educational system that provides each full development of his capabilities and abilities; democratization of the educational process, the elimination of uniformity in training, providing students the freedom to choose the elements of the educational process; creating conditions for training and education, adequate individual needs and optimal diversification for the overall development of students; the formation and development of individuality, independence and creative potential.